Thin solid electrolyte interface on chemically bonded Sb2Te3/CNT composite anodes for high performance sodium ion full cells. (May 2020) - Ihsan-Ul-Haq, Muhammad; Huang, He; Wu, Junxiong; Cui, Jiang; Yao, Shanshan; Chong, Woon Gie; Huang, Baoling; Kim, Jang-Kyo
Abstract: Nanostructured metal chalcogenides (MCs) and their composites are studied for high performance sodium-ion batteries (SIBs). Herein, we report the assembly of an emerging MC, Sb2 Te3, with functionalized carbon nanotubes (CNTs) to form composite anodes. The role of oxygenated functional groups on CNTs in fostering the chemical interactions with Sb2 Te3 for enhanced structural integrity of electrodes is elucidated by density functional theory combined with ab-initio molecular dynamics simulations and X-ray photoelectron spectroscopy analysis. Remarkably, cryogenic transmission electron microscopy (TEM) analysis reveals a uniform and thin solid electrolyte interface (SEI) layer of ~19.1 nm on the Sb2 Te3 /CNT composite while the neat Sb2 Te3 presents an irregular and ~67.3 nm thick SEI. The ex-situ X-ray diffraction (XRD) and ex-situ / in-situ TEM analyses offer mechanistic explanations of phase transition and volume changes during sodiation. The Sb2 Te3 /CNT composite electrode with an optimal content of 10 wt% CNTs delivers excellent reversible gravimetric and volumetric capacities of 422 mA h g −1 and 1232 mA h cm −3, respectively, at 100 mA g −1 with ~97.5% capacity retention after 300 cycles. The excellent high-rate capability of 318 mA h g −1 at 6400 mA g −1 corroborates the structural robustness of the composite electrode. Sodium-ion full cells (SIFCs) are assembled by pairing the above anode with a Na3 V2 (PO4 )2 F3 cathode, which exhibit remarkable energy density of ~229 Wh kg −1 at 0.5 C and excellent cyclic stability of over 71% and 66% capacity retention at 5 C and 10 C, respectively, after 200 cycles. Even at 40 C, an ultrahigh power density of 5384 W kg −1 is delivered. Furthermore, the pouch-type SIFCs prove excellent flexibility with ~85% capacity retention after 1000 bending cycles and satisfactory operation under temperatures ranging from 40 to −20 °C. The design strategy developed here can also be employed to other electrode materials to achieve better SEI stability and excellent Na storage performance. Graphical abstract: The Na-ion full cells prepared from topological insulator Sb2 Te3 /functionalized CNTs deliver exceptional energy and power densities with demonstrated cyclic stability, enhanced flexibility and operation capability at different service temperatures. Cryogenic TEM reveals the formation of a thin and uniform solid electrolyte interface on the composite electrodes. DFT calculations and AIMD simulations corroborate the strong chemical interactions at the heterointerfaces of Sb2 Te3 and functionalized CNTs. Image 1 Highlights: Cryogenic TEM is employed to reveal the thickness and morphology of SEI layer on the electrodes. DFT calculations elucidate the role of different oxygenated functional groups on carbon surface to enable chemical bonds in Sb2 Te3 /CNT composites. Small volume expansion of composite electrode (~142%) upon sodiation is observed by in-situ TEM analysis. Sodium ion full cells deliver high energy density of ~229 Wh kg −1 at 0.5 C and outstanding power density of 5384 W kg −1 at 40 C. Over 84% capacity retention of pouch-type sodium ion full cells under 1000 bending cycles and their stable operation at service temperatures of 40, 20, 0 and −20 °C are demonstrated.